Republic and Constitution: a study about the republican principle, basis of the Democratic Rule of Law (Research, Society and Development, 2020)
The Democratic Rule of Law, established in Brazil by the 1988 Constitution, is based on the republican principle. Its concept, however, resembles that of some other principles, so it is also necessary to study the surrounding issues, such as the republic itself, constitutional principles and constitutionalism. The aim of this paper is to analyze the republican principle in its entirety, as well as the historical concept that surrounds it. As a structuring principle, the republican principle must be respected in its entirety by those who hold political office, since in the Public Administration, the collective interest must come first, always seeking the common good. Otherwise, the rulers will be violating him. Society, in turn, must understand the role that the republican principle plays in our system, so as to better choose its representatives and charge them always according to the interests of the majority.